Thioredoxin Profiling of Multiple Thioredoxin-Like Proteins in Staphylococcus aureus - Peng, Hui; Zhang, Yixiang; Trinidad, Jonathan C.; Giedroc, David P. (Frontiers in Microbiology, 2018)
Hydrogen sulfide (H2S) is thought to signal through protein S-sulfuration (persulfidation; S-sulfhydration) in both mammalian systems and bacteria. We previously profiled proteome S-sulfuration in Staphylococcus aureus (S. aureus) and identified two thioredoxin-like proteins, designated TrxP and TrxQ, that were capable of reducing protein persulfides as a potential regulatory mechanism. In this study, we further characterize TrxP, TrxQ and the canonical thioredoxin, TrxA, by identifying candidate protein substrates in S. aureus cells using a mechanism-based profiling assay where we trap mixed disulfides that exist between the attacking cysteine of a FLAG-tagged Trx and a persulfidated cysteine on the candidate substrate protein in cells. Largely non-overlapping sets of four, 32 and three candidate cellular substrates were detected for TrxA, TrxP, and TrxQ, respectively, many of which were previously identified as global proteome S-sulfuration targets including for example, pyruvate kinase, PykA. Both TrxA (kcat = 0.13 s-1) and TrxP (kcat = 0.088 s-1) are capable of reducing protein persulfides on PykA, a model substrate detected as a candidate substrate of TrxP; in contrast, TrxQ shows lower activity (kcat = 0.015 s-1). This work reveals that protein S-sulfuration, central to H2S and reactive sulfur species (RSS) signaling, may impact cellular activities and appears to be regulated in S. aureus largely by TrxP under conditions of sulfide stress.